Retinal vessel leakage at high altitude - Willmann, Gabriel; Fischer, M. Dominik; Schatz, Andreas; Schommer, Kai; Gekeler, Florian (The journal of the American Medical Association, 2013)
To the Editor: Exposure to high altitude can cause acute mountain sickness (AMS) and, in severe cases, cerebral or pulmonary edema. Capillary leakage has been hypothesized to play a role in the pathogenesis of AMS, although the mechanism of altitude-related illnesses remains largely unknown. As a directly observable part of the brain, the retina offers a window to study altitude-related vascular changes of the central nervous system.High-altitude retinopathy is characterized by optic disc edema, retinal hemorrhages, cotton wool spots, and increased tortuosity and dilation of retinal vessels. Vessel leakage in the retinal periphery has not been investigated. Our objective was to assess retinal vessel integrity at high altitude using fluorescein angiography.